2006
DOI: 10.1097/01.ico.0000214215.75496.a5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Clinical In Vivo Confocal Microscopic and Ex Vivo Histopathologic Findings of Salzmann Nodular Degeneration

Abstract: In vivo confocal microscopy confirmed the clinicopathologic findings of Salzmann's nodular degeneration. Observations by in vivo confocal microscopy were consistent with the histopathologic descriptions of SND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 14 publications
5
21
1
5
Order By: Relevance
“…Within the entire follow-up period up to 31 months, we did not experience any complications and epithelial healing seemed to be normal. Our findings after treatment correspond well with findings of SND by other authors in earlier literature [13].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Within the entire follow-up period up to 31 months, we did not experience any complications and epithelial healing seemed to be normal. Our findings after treatment correspond well with findings of SND by other authors in earlier literature [13].…”
Section: Discussionsupporting
confidence: 95%
“…The first report on the use of topical MMC for the treatment of patients with recurrent, visually disabling subepithelial fibrosis after radial keratotomy (RK) and photorefractive keratectomy (PRK) was by Majmudar et al [10] in 2000. Meanwhile, MMC in combination with PTK was also described by other authors [13,19,20].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The new modalities of in vivo imaging are transforming the need for histopathologic correlation. Meltendorf et al 6 have demonstrated comparable findings for Salzmann nodular degeneration between histopathology and in vivo confocal microscopy. Classical histopathologic findings of Salzmann nodular degeneration have been described as an accumulation of a dense basement membrane-like material overlying stromal disorganization that obliterates Bowman layer and is covered by a thinned layer of epithelium.…”
Section: Discussionmentioning
confidence: 62%
“…Das Epithel über den Knötchen ist verdünnt und verändert [28,38,45,49]. Die Auflösung der ursprünglichen Bowman und ihren Ersatz durch pathologisches Dystrophiegewebe hatte Salzmann fehlinterpretiert als einen Prozess, der durch einen resorptiven, entzündlichen Pannus verursacht worden sei.…”
Section: Histopathologische Einordnung Der Salzmann-dystrophie Bei Deunclassified